Effect of ageing on the mechanical and chemical properties of binder from RAP treated with bio-based rejuvenators. (15th May 2018) - Cavalli, M.C.; Zaumanis, M.; Mazza, E.; Partl, M.N.; Poulikakos, L.D.
Abstract: Reclaimed asphalt pavement (RAP) is harder than virgin bitumen due to ageing and it needs to be rejuvenated. Three bio-based rejuvenators are used and the rejuvenating effects are evaluated. Rheological tests show how the rejuvenators may restore the mechanical properties of RAP binder. An ageing index is proposed to show that the rejuvenators are affected differently by ageing. Despite their addition, physio-chemical oxidation did not reverse. Mechanical changes were not caused by chemical changes at functional groups level but a rearrangement of polar/nonpolar components. The results show that considering the effect of aging is vital in identifying how rejuvenators affect the RAP binder chemically and mechanically. Graphical abstract: Highlights: Bio-based rejuvenators were able to restore the mechanical properties of RAP binder. Ageing index demonstrated how various rejuvenators had a different impact on the aged RAP. No changes at functional groups level was seen after rejuvenation. Due to ageing a rearrangement of polar/nonpolar components was observed.